2019
DOI: 10.1186/s12916-018-1244-y
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of multi-level stigma interventions: state of the science and future directions

Abstract: Background Researchers have long recognized that stigma is a global, multi-level phenomenon requiring intervention approaches that target multiple levels including individual, interpersonal, community, and structural levels. While existing interventions have produced modest reductions in stigma, their full reach and impact remain limited by a nearly exclusive focus targeting only one level of analysis. Methods We conducted the first systematic review of original researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
198
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(209 citation statements)
references
References 42 publications
6
198
1
4
Order By: Relevance
“…The tension therefore emerges between the immediate-and faster-work of providing information in the midst of the COVID-19 pandemic and the need for long-term investment in reducing social inequities. Stigma-reduction strategies for HIV and other health issues have largely targeted intrapersonal and interpersonal dimensions, far fewer have addressed structural factors such as legal issues, policies, and rights [36]. Interventions should address both drivers (knowledge, misinformation) and facilitators (health policies, institutional practices) [37].…”
Section: Tensions Between Stigma Mitigation and Covid-19 Public Healtmentioning
confidence: 99%
“…The tension therefore emerges between the immediate-and faster-work of providing information in the midst of the COVID-19 pandemic and the need for long-term investment in reducing social inequities. Stigma-reduction strategies for HIV and other health issues have largely targeted intrapersonal and interpersonal dimensions, far fewer have addressed structural factors such as legal issues, policies, and rights [36]. Interventions should address both drivers (knowledge, misinformation) and facilitators (health policies, institutional practices) [37].…”
Section: Tensions Between Stigma Mitigation and Covid-19 Public Healtmentioning
confidence: 99%
“…Approaches to addressing stigma in the context of promoting well-being and disease prevention exist and likely provide relevant tools applicable to addressing COVID-19. Interventions to address stigma have been developed that target individuals, health care workers, communities, and social figures, which will likely find new purpose in COVID-19 (Andersson et al, 2020;Rao et al, 2019;Stangl et al, 2013).…”
Section: Interpersonal Factorsmentioning
confidence: 99%
“…The perceived dangerousness, for example, is amenable to following swift advancement in treatment and control [24]. Therefore, several studies suggested the need to conduct multilayered intervention targeting factors at the individual, interpersonal, community, institution, and structural levels to reduce stigma [41,42].…”
Section: Discussionmentioning
confidence: 99%